The chlamydial transcriptional regulator Euo is a key switch in cell form developmental progression but is not involved in the committed step to the formation of the infectious form - Cody R. Appa; Nicole A. Grieshaber; Hong Yang; Anders Omsland; Sean McCormick; Travis J. Chiarelli; Scott S. Grieshaber (mSphere)
ABSTRACT Bacteria in the genus Chlamydia are a significant health burden worldwide. They infect a wide range of vertebrate animals, including humans and domesticated animals. In humans, C. psittaci can cause zoonotic pneumonia, while C. pneumoniae causes a variety of respiratory infections. Infections with C. trachomatis cause ocular or genital infections. All chlamydial species are obligate intracellular bacteria that replicate exclusively inside of eukaryotic host cells. Chlamydial infections are dependent on a complex infection cycle that depends on transitions between specific cell forms. This cycle consists of cell forms specialized for host cell invasion, the elementary body (EB), and a form specialized for intracellular replication, the reticulate body (RB). In addition to the EB and RB, there is a transitionary cell form that mediates the transformation between the RB and the EB, the intermediate body (IB). In this study, we ectopically expressed the regulatory protein Euo and showed that high levels of expression resulted in reversible arrest of the development cycle. The arrested chlamydial cells were trapped phenotypically at an early IB stage of the cycle. These cells had exited the cell cycle but had not shifted gene expression from RB like to IB/EB like. This arrested state was dependent on continued expression of Euo. When ectopic expression was reversed, Euo levels dropped in the arrested cells which led to the repression of native Euo expression and the resumption of the developmental cycle. Our data are consistent with a model where Euo expression levels impact IB maturation to the infectious EB but not the production of the IB form.IMPORTANCEBacterial species in the Chlamydiales order infect a variety of vertebrate animals and are a global health concern. They cause various diseases in humans, including genital and respiratory infections. The bacteria are obligate intracellular parasites that rely on a complex infectious cycle involving multiple cell forms. All species share the same life cycle, transitioning through different states to form the infectious elementary body (EB) to spread infections to new hosts. The Euo gene, encoding a DNA-binding protein, is involved in regulating this cycle. This study showed that ectopic expression of Euo halted the cycle at an early stage. This arrest depended on continued Euo expression. When Euo expression was reversed, the developmental cycle resumed. Additionally, this study suggests that high levels of Euo expression affect the formation of the infectious EB but not the production of the cell form committed to EB formation.